Karakteristik Kecelakaan di Jalan Bypas Bandar Lampung - hidayah, ulfa; Putra, Sasana; Karami, Muhammad (Universitas Lampung, 2018)
The purposes of this study were to analyze the relationship between the characteristics of accidents and road safety facilities such as road signs, road markings, and lighting lights, and to analyze the characteristics of traffic accidents on Soekarno-Hatta Bypass Road included type accident and factors causing of the accident. The surveys in the field were conducted to obtain the primary data about road safety facilities, however the secondary data were obtained from the Bandar Lampung police station in the form of accident data per month from 2014-2017. The results showed that there were still inadeguate road safety facilities on the Soekarno-Hatta Bypass road, such as lighting and road markings.The characteristics of accidents based on the factors that cause the accidents were human factors (85.28%). The types of accidents were are front-rear accidents (28.8%). Keywords: Accident Characteristics, Arterial Road, Road Safety Facilities